2008
DOI: 10.1007/s10620-008-0635-x
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Overview of a Retrospective Study About Adult Intussusceptions: Focusing on Discrepancies Among Previous Studies

Abstract: This study was to determine clinical entity of adult intussusception, focusing on discrepancies among previous studies and to retrospectively investigate the factors associated with malignancy and survival for 10 years. In our study, 3.7% (N = 42) of intussusception were adults. The most common symptom was acute abdominal pain (64.3%). Enteric, ileocolic, ileocecal, and colocolic intussusception included 52.4, 9.5, 14.3, and 23.8% of patients, respectively. Two patients (9.1%) with enteric (N = 22), no patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 18 publications
0
21
0
3
Order By: Relevance
“…Primary or idiopathic adult intussusception accounts for only 10 % of cases and is more likely to develop in the small intestine. Up to 90 % of occurrences in adults have a leading point, which is defined as a welldefinable pathological abnormality [6].…”
Section: Discussionmentioning
confidence: 99%
“…Primary or idiopathic adult intussusception accounts for only 10 % of cases and is more likely to develop in the small intestine. Up to 90 % of occurrences in adults have a leading point, which is defined as a welldefinable pathological abnormality [6].…”
Section: Discussionmentioning
confidence: 99%
“…Ileocolic intussusception associated to Salmonella typhimurium infection has been previously reported on only one occasion, constituting an extremely uncommon occurrence [4]. Ileocolic intussusception accounts for less than 10% of all adult intussusceptions, being a rather uncommon condition [3].We discuss a case of ileocolic intussusception associated with infectious enterocolitis caused by Salmonella enteritidis.…”
Section: Introductionmentioning
confidence: 94%
“…The exact mechanism that precipitates intussusception is still unknown, but it is believed that any lesion in the bowel wall or irritant contents within the bowel lumen may alter the normal peristaltic pattern, starting the process of invagination [1]. Adult intussusception is rare, accounting for only 5% or less of all reported cases [2,3]. In contrast to pediatric intussusception, 90% of adult intussusceptions will have a leading point, usually a malign neoplasm, while the remaining 10% are considered idiopathic [2].…”
Section: Introductionmentioning
confidence: 99%
“…It is usually a condition of the pediatric population and the adult form is regarded as a rare condition that constitutes approximately 5% of all intussusceptions and it accounts for 1% of all adult intestinal obstructions. 1 Adult intussusceptions are generally the result of benign masses such as various polyps, adenomas and lipomas but malignant lesions such as adenocarcinoma of the bowel are nevertheless may be etiological factors. 2 Most studies reported that 60-80% of enteric intussusceptions were benign and 50-65% of colonic intussusceptions were malignant.…”
Section: Introductionmentioning
confidence: 99%
“…2 Most studies reported that 60-80% of enteric intussusceptions were benign and 50-65% of colonic intussusceptions were malignant. 1 Lipoma of the bowel wall is an infrequent entity and it may very well be a ground for adult type intussusception. They are usually clinically silent and may end up developing intussusceptions when they reach to several centimetres in size.…”
Section: Introductionmentioning
confidence: 99%